MRI Grading as a Predictive Tool for Histopathological Grading in Supratentorial Meningiomas: A Prospective Study (Bangladesh Journal of Neurosurgery, 2026)
Introduction: Meningiomas are common intracranial tumors, and accurate preoperative  assessment is crucial for optimal management. Magnetic resonance imaging (MRI) is a  valuable tool for assessing meningiomas, and recent studies have suggested that MRI  features may be predictive of histopathological grade. Objective: To evaluate the utility of  MRI grading as a predictive tool for histopathological grading in supratentorial meningiomas.  Methods: This cross-sectional study was conducted from July 2019 to December  2020 at the Department of Neurosurgery of Dhaka Medical College and Hospital. A total  of 43 patients with supratentorial meningiomas underwent resection. Preoperative MRI  features were analyzed, and the relationships between MRI features and WHO  histopathological grade were quantitatively scored. Results: Most of the 43 patients  included in the study were female (67.4%). The mean age was 52.3 years. WHO grade I  meningiomas were the most common (58.1%), followed by grade II (23.3%) and grade III  (18.6%). Specific MRI features, including tumor size, location, and enhancement pattern,  are significantly associated with histopathological grade. The quantitative scoring system  demonstrated a high predictive value for distinguishing between low and high-grade  meningiomas. Conclusions: MRI grading shows promise as a predictive tool for  histopathological grading in supratentorial meningiomas. Further research with larger  sample sizes is warranted to validate these findings and potentially integrate MRI grading  into routine clinical practice.Bang. J Neurosurgery 2025; 14(2):  132-137